2012
DOI: 10.1093/annonc/mds203
|View full text |Cite
|
Sign up to set email alerts
|

The impact of second to sixth line therapy on survival of relapsed ovarian cancer after primary taxane/platinum-based therapy

Abstract: A maximum of three lines of subsequent relapse treatment seems to be beneficial for patients with recurrent ovarian cancer. Optimal primary tumor debulking and platinum sensitivity remain independent prognostic factors even after more frequent relapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
232
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(251 citation statements)
references
References 30 publications
15
232
1
3
Order By: Relevance
“…It is noteworthy that similar levels of ORRs were also observed with the use of taxanes and PLD as monotherapies (Tables 2 and 3). Although published data on ORRs are scarce in patients with EOC carrying germline BRCA1/2 mutations in the third-line (and later) settings, the ORRs observed in this study seem to be in keeping with other phase II data for the same regimens in the general EOC population (26). Overall, these data point to significant differences in the mechanisms of resistance between PARPi and chemotherapy including platinum-based agents.…”
Section: Discussionsupporting
confidence: 87%
“…It is noteworthy that similar levels of ORRs were also observed with the use of taxanes and PLD as monotherapies (Tables 2 and 3). Although published data on ORRs are scarce in patients with EOC carrying germline BRCA1/2 mutations in the third-line (and later) settings, the ORRs observed in this study seem to be in keeping with other phase II data for the same regimens in the general EOC population (26). Overall, these data point to significant differences in the mechanisms of resistance between PARPi and chemotherapy including platinum-based agents.…”
Section: Discussionsupporting
confidence: 87%
“…3 Platinum retreatment is used in patients in whom there is an assumed platinum sensitivity, with diminishing effectiveness and a cumulative increase in toxicity. 3 Niraparib is a highly selective inhibitor of poly(adenosine diphosphate [ADP]-ribose) polymerase (PARP) 1/2, 4 nuclear proteins that detect DNA damage and promote its repair. Clinical studies have evaluated PARP inhibitors in patients with recurrent ovarian cancer, including those with germline BRCA mutations, platinum-sensitive disease, or both.…”
mentioning
confidence: 99%
“…In contrast, treatments beyond second-line therapy are rather heterogeneous, and data about response rate and survival are controversial and even disappointing. Recently, Hanker et al [18] in a retrospective multicenter analysis found that the application of 3 lines of relapse treatment seems to be the maximum acceptable therapy and that additional lines of subsequent treatment appear not to be beneficial for all ROC patients. On the other hand, it should also be considered that most patients prefer subsequent chemotherapy even with a small survival benefit [19] .…”
Section: Discussionmentioning
confidence: 99%